2007
DOI: 10.1016/j.cardfail.2006.11.009
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Level of Pentosidine, an Advanced Glycation End Product (AGE), is a Risk Factor of Patients with Heart Failure

Abstract: Background: Pentosidine, one of the advanced glycation end products (AGE), is generated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 35 publications
1
84
0
1
Order By: Relevance
“…In support of this suggestion, an association has been shown between AGE accumulation measured as skin AF and peripheral arterial disease independent of diabetes status, and increasing AGEs (measured as serum pentosidine) have been associated with poor prognosis in people with heart failure (29,30). In the context of CKD, Hartog et al (16) showed correlation between skin AF and poorer diastolic function in a crosssectional study of peritoneal dialysis and hemodialysis patients, and Meerwaldt et al (20) identified independent associations between skin AF and cardiovascular as well as all-cause mortality in a prospective cohort of 109 patients on hemodialysis.…”
Section: Discussionmentioning
confidence: 91%
“…In support of this suggestion, an association has been shown between AGE accumulation measured as skin AF and peripheral arterial disease independent of diabetes status, and increasing AGEs (measured as serum pentosidine) have been associated with poor prognosis in people with heart failure (29,30). In the context of CKD, Hartog et al (16) showed correlation between skin AF and poorer diastolic function in a crosssectional study of peritoneal dialysis and hemodialysis patients, and Meerwaldt et al (20) identified independent associations between skin AF and cardiovascular as well as all-cause mortality in a prospective cohort of 109 patients on hemodialysis.…”
Section: Discussionmentioning
confidence: 91%
“…Serum AGE levels have been demonstrated as independent predictors of both the severity and prognosis in heart failure patients [14,55] . Plasma pentosidine levels, one of the crosslinking AGEs, has been shown to be an independent predictor of both re-hospitalization and mortality in heart failure patients independent from other known risk factors such as brain natriuretic peptide (BNP), age, renal function and New York Heart Association (NYHA) functional class [55] .…”
Section: Complications Of Diabetesmentioning
confidence: 99%
“…Plasma pentosidine levels, one of the crosslinking AGEs, has been shown to be an independent predictor of both re-hospitalization and mortality in heart failure patients independent from other known risk factors such as brain natriuretic peptide (BNP), age, renal function and New York Heart Association (NYHA) functional class [55] . Similarly, plasma levels of N-CML, one of the most prevalent antigenic AGEs in sera of diabetic patients, have been shown to correlate with NYHA functional class and predict outcomes in patients with systolic heart failure [14] .…”
Section: Complications Of Diabetesmentioning
confidence: 99%
“…However, it was reported that a higher pentosidine concentration was related to a poor outcome of cerebral infarction [22] and cardiac events [20,23], indicating the possibility that pentosidine might play pathophysiological roles, such as induction of oxidative stress and endothelial dysfunction [24,25], in the progression of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%